Contemporary Debates in Education: Theoretical Perspectives on Pedagogy, Technology, and Society: Contemporary Debates in Education: Theoretical Perspectives on Pedagogy, Technology, and Society - Fontaneda Amo, Carmen; Gil Cantero, Fernando (Revista Complutense de Educación, 2026)
Contemporary education is shaped by a set of ongoing theoretical debates, including the relationship between theory and practice, the tensions between humanism and posthumanism, and the evolution from critical to post-critical pedagogy. This article examines these controversies from the perspective of educational theory in order to clarify their implications for understanding education in current social and intellectual contexts. The analysis develops a critical interpretation of these debates and proposes a normative framework aimed at strengthening pedagogical reflection. The findings suggest that the decline of theoretical thinking may lead to forms of pedagogical anti-intellectualism, while the uncritical adoption of technological developments raises important questions about the role and limits of education. In addition, the relationship between critical and post-critical perspectives is examined as a way to address ideological tensions without losing sight of the formative value of education. The study contributes by offering an integrated interpretation of these debates and highlighting their relevance for contemporary pedagogical thought.